Phosphorylation of a splice variant of collapsin response mediator protein 2 in the nucleus of tumour cells links cyclin dependent kinase-5 to oncogenesis. Issue 1 (December 2015) - Grant, Nicola; Coates, Philip; Woods, Yvonne; Bray, Susan; Morrice, Nicholas; Hastie, C.; Lamont, Douglas; Carey, Francis; Sutherland, Calum
Abstract Background Cyclin-dependent protein kinase-5 (CDK5) is an unusual member of the CDK family as it is not cell cycle regulated. However many of its substrates have roles in cell growth and oncogenesis, raising the possibility that CDK5 modulation could have therapeutic benefit. In order to establish whether changes in CDK5 activity are associated with oncogenesis one could quantify phosphorylation of CDK5 targets in disease tissue in comparison to appropriate controls. However the identity of physiological and pathophysiological CDK5 substrates remains the subject of debate, making the choice of CDK5 activity biomarkers difficult. Methods Here we usein vitro and in cell phosphorylation assays to identify novel features of CDK5 target sequence determinants that confer enhanced CDK5 selectivity, providing means to select substrate biomarkers of CDK5 activity with more confidence. We then characterize tools for the best CDK5 substrate we identified to monitor its phosphorylation in human tissue and use these to interrogate human tumour arrays. Results The close proximity of Arg/Lys amino acids and a proline two residues N-terminal to the phosphorylated residue both improve recognition of the substrate by CDK5. In contrast the presence of a proline two residues C-terminal to the target residue dramatically reduces phosphorylation rate. Serine-522 of Collapsin Response Mediator-2 (CRMP2) is a validated CDK5 substrate with many of these structural criteria. We generate and characterise phosphospecific antibodies to Ser522 and show that phosphorylation appears in human tumours (lung, breast, and lymphoma) in stark contrast to surrounding non-neoplastic tissue. In lung cancer the anti-phospho-Ser522 signal is positive in squamous cell carcinoma more frequently than adenocarcinoma. Finally we demonstrate that it is a specific and unusual splice variant of CRMP2 (CRMP2A) that is phosphorylated in tumour cells. Conclusions For the first time this data associates altered CDK5 substrate phosphorylation with oncogenesis in some but not all tumour types, implicating altered CDK5 activity in aspects of pathogenesis. These data identify a novel oncogenic mechanism where CDK5 activation induces CRMP2A phosphorylation in the nuclei of tumour cells.